2020
DOI: 10.3390/ijerph17113825
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Thyroid and Glycemic Status and Food Intake in Children with Excess Weight Who Were Submitted for a Multi-Component School Intervention for 16 Months

Abstract: We investigated if children with excess weight who submitted to two types of intervention at school for 16 months showed improvements in thyroid and glycemic function and food intake. Children (8–11 years) with a body mass index-for-age (BMI/A) of ≥1 Z score were divided into two groups: Treatment 1 (n = 73) involved motivation to adopt healthier lifestyle; Treatment 2 (n = 103) involved performing weekly nutritional education, motivational, and physical activities at school. A semi-quantitative food frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…28 Exercise, or any form of regular physical activity leads to changes in BMI related to thyroid hormones. 9,25,27 No significant study evidenced thyroid hormones returning to normal within the intervention period or post it. However, studies showed some changes in thyroid hormones due to exercise or physical activity linked with weight loss.…”
Section: Hypothyroidismmentioning
confidence: 97%
See 3 more Smart Citations
“…28 Exercise, or any form of regular physical activity leads to changes in BMI related to thyroid hormones. 9,25,27 No significant study evidenced thyroid hormones returning to normal within the intervention period or post it. However, studies showed some changes in thyroid hormones due to exercise or physical activity linked with weight loss.…”
Section: Hypothyroidismmentioning
confidence: 97%
“…9 Furthermore, subclinical hypothyroidism shows increased TSH concentrations with normal fT3 and free T4(fT4) concentrations. 27 Wolters et al (2012) studied the relationship between TSH and thyroid hormones fT3 fT4 and weight status, as well as their changes, during and after lifestyle intervention. The baseline values in the study of TSH and fT3 were high, and the study results showed differences in TSH and fT3 but not fT4 during the intervention period, which was not significant.…”
Section: Hypothyroidismmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that the decrease in these hormones aims to reduce energy expenditure. In contrast, excess weight increases insulin (17) , leptin (18) and thyroid hormones (19) . Some authors have suggested that the increase in leptin and thyroid hormones could counteract the excess energy stored and facilitate increased expenditure (20,21) .…”
Section: Introductionmentioning
confidence: 97%